2015
DOI: 10.5624/isd.2015.45.4.213
|View full text |Cite
|
Sign up to set email alerts
|

Cephalometric landmark variability among orthodontists and dentomaxillofacial radiologists: a comparative study

Abstract: PurposeThe aim this study was to compare the accuracy of orthodontists and dentomaxillofacial radiologists in identifying 17 commonly used cephalometric landmarks, and to determine the extent of variability associated with each of those landmarks.Materials and MethodsTwenty digital lateral cephalometric radiographs were evaluated by two groups of dental specialists, and 17 cephalometric landmarks were identified. The x and y coordinates of each landmark were recorded. The mean value for each landmark was consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 18 publications
4
50
1
2
Order By: Relevance
“…The difference in performance between the doctor1-trained and the doctor2-trained systems does not only show that the FALA system replicates the manual annotation accuracy but also highlights that there may be large annotation variations in clinical practice 3 . The latter may be due to different levels of training or experience, and other circumstances such as time pressure and physical condition (e.g.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The difference in performance between the doctor1-trained and the doctor2-trained systems does not only show that the FALA system replicates the manual annotation accuracy but also highlights that there may be large annotation variations in clinical practice 3 . The latter may be due to different levels of training or experience, and other circumstances such as time pressure and physical condition (e.g.…”
Section: Discussionmentioning
confidence: 88%
“…Currently in clinical practice, cephalometric landmark positions are identified manually or semi-automatically which is very tedious, time-consuming and prone to inconsistencies within and across orthodontists. Varying levels of orthodontic training and experience may have an impact on inter -observer variations, and time-constraints and other commitments may have an impact on intra -observer consistency 3 .…”
mentioning
confidence: 99%
“…The landmarks of Gonion, Nasion, Orbitale, and Anterior Nasal Spine (ANS) showed the most considerable median Euclidean distances for both intra- and inter-observer measurements according to Katkar et al 2013 [ 31 ]. According to Durao APR et al, the Gnathion (Gn) point was the least reliable landmark for orthodontists, while the Orbitale (Or) was the least reliable landmark for dentomaxillofacial radiologists [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various previous angles have used points with lower reproducibility like point B and condylion (Co), which reduces authenticity of these parameters. 24 Moreover, localization of Co is difficult due to differential magnification inherent in bilateral structures and resulting image distortion. 25 Several researchers have shown that Co cannot be accurately and consistently located on the closed-mouth lateral cephalogram.…”
Section: Discussionmentioning
confidence: 99%